2017
DOI: 10.1111/eip.12405
|View full text |Cite
|
Sign up to set email alerts
|

Achievement motivation in early schizophrenia: Relationship with symptoms, cognition and functional outcome

Abstract: Our results serve to highlight the occurrence and prevalence of motivational deficits in patients with schizophrenia who are in the early stages of their illness. Subjective accounts of motivation in this population were found to be related to important outcomes such as community functioning, highlighting the importance of this domain of illness. Targeting these deficits early in the course of the illness offers the potential to curb potential prospective poor outcomes and sets the stage for recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…In contrast to our study, Liemburg et al (2013) included subjects with recent onset of psychosis and did not rule out secondary negative symptoms. It has been suggested that disturbance of volition is more prevalent in the early stages of schizophrenia (Fervaha et al, 2017) and associated with depression (Krynicki et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to our study, Liemburg et al (2013) included subjects with recent onset of psychosis and did not rule out secondary negative symptoms. It has been suggested that disturbance of volition is more prevalent in the early stages of schizophrenia (Fervaha et al, 2017) and associated with depression (Krynicki et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Motivational deficits in patients with schizophrenia are persistent, are prevalent from the earliest stages of the disease, and may uniquely predict outcomes beyond other symptoms . Across several neuropsychiatric disorders, including schizophrenia, amotivation is associated with abnormal functioning of frontal‐striatal circuits involving the dorsolateral prefrontal cortex, anterior cingulate cortex, and ventral striatum (VS) .…”
Section: Introductionmentioning
confidence: 99%
“…Such behaviours have traditionally been assessed via questionnaire-based measures, aimed at assessing pathological disruptions in motivation. These include either subsets of inventories [34] or specific scales [35,36]. However, in addition to limitations associated with such assessments such as recall bias, linking these to assessments used in experimental animals such as PR and ERC is problematic [37 ].…”
Section: Translating Animal Motivational Assessments To Humansmentioning
confidence: 99%